Synthesis of Some New Pyrimidine-Azitidinone Analogues and Their Antioxidant, In Vitro Antimicrobial, and Antitubercular Activities - Mallikarjunaswamy Chandrashekaraiah; Mallesha Lingappa; Vathsala Deepu Channe Gowda; Doddamedur Giddegowda Bhadregowda (Journal of Chemistry)
A series of 1-(3-(4-(pyridin-3-yl)pyrimidin-2-ylamino)-4-methylphenyl)-3-chloro-4-(2-mercaptoquinolin-3-yl)azetidin-2-one (7a-j) have been synthesized from the condensation of aromatic amines with N-phenylacetamide. The thione nucleus formed from 2-chloroquionoline-3-carbadehyde using sodium sulphide in dimethyl formamide (DMF) was followed by the reaction with pyrimidine amine to form the Schiff base intermediates. Attempt has been made to derive final azetidinone analogues from Schiff bases by using chloroacetyl chloride. The newly synthesized analogues were examined for the antimicrobial activity against some bacterial and fungal strains and in vitro antituberculosis activity against mycobacterium tuberculosis. These observations provide some predictions to design further antibacterial and antituberculosis active compounds prior to their synthesis according to molecular studies.